A re-usable 3D-printed training model for the endodontic management of dental trauma in immature teeth - Maier, Eva; Zentgraf, Jan; Angele, Eveline; Zorzin, José Ignacio; Taschner, Michael; Widbiller, Matthias; Galler, Kerstin Martina; Schratzenstaller, Thomas (International Endodontic Journal, 2025)
Aim: To develop a 3D-printed model enabling treatment simulation of trauma-related endodontic and restorative procedures like revitalization or placement of an apical plug on teeth with incomplete root formation. Methodology: To generate a realistic training model suitable for trauma-related simulations, CT-Data sets were segmented, combined, adjusted and optimized using computer-aided design features. Specific focus was on optimally reflecting characteristics of immature teeth like open apical foramina and thin root walls. For reflection of the revitalization process, a set-up including a tube filled with red liquid under pressure was developed to be perforated during the procedure by the trainee, simulating bleeding from the apical papilla into the root canal system. Design was based on a combination of cost-effective simple parts combined with 3D-printed components to achieve maximal accessibility, exchangeability and re-usability. Model assembly and preparation were described in step-by-step instructions. Results: As a result of the developmental process, the presented model qualifies for the training of the endodontic management of complications on immature teeth after dental trauma. Step-by-step descriptions aligned with the clinical procedures are performable for a revitalization procedure, for pulpotomy followed by fragment re-attachment and splint application and for placement of an apical plug using hydraulic calcium silicate cements. Conclusions: The model successfully achieved its intended objectives, so that it may be used in the future in various dental trauma treatment simulations for undergraduate and postgraduate education on the endodontic management of trauma-related therapies in immature teeth. Its common manufacturing process, affordability and re-usability support accessibility and sustainability.
CRIS-Team Scopus Importer:2025-04-18
Keywords: 3D-printing; dental education; dental traumatology; immature teeth; revitalization; training model